2015
DOI: 10.1007/s00339-015-9246-5
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of laser-induced transverse thermoelectric voltages in the perovskite Nd2−x Ce x CuO4 thin films

Abstract: Large laser-induced thermoelectric voltages (LITVs) are measured in the electron-doped Nd 2-x Ce xCuO 4 thin films grown on the vicinal-cut SrTiO 3 substrates by pulsed laser deposition. The dependence of LITV signals upon the doping carrier density is investigated by changing the Ce content of the films. The optimum Ce dopant corresponding to the largest voltage is found and is attributed to the two-dimensional transport behaviors of the localized electrons. The shorter laser irradiation always induces the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In a recent study, Firmicutes, Thermotogae, Deltaproteobacteria, and Synergistetes were observed under sulfate-reducing and high-temperature conditions (Xiong et al, 2015). Accordingly, Firmicutes and Thermotogae were found to be abundant in our sulfate-reducing community, as well as in our methanogenic community.…”
Section: Comparison Of the Two High-pressure-enriched Communities To ...supporting
confidence: 59%
“…In a recent study, Firmicutes, Thermotogae, Deltaproteobacteria, and Synergistetes were observed under sulfate-reducing and high-temperature conditions (Xiong et al, 2015). Accordingly, Firmicutes and Thermotogae were found to be abundant in our sulfate-reducing community, as well as in our methanogenic community.…”
Section: Comparison Of the Two High-pressure-enriched Communities To ...supporting
confidence: 59%
“…As expected, A ‐site Ba/Nd substitution can greatly expand the lattice in c ‐axis, giving rise to the decoupling of 2D CuO 2 planes, which drastically increases the structural bidimensionality in terms of, e.g., charge transport and thermoelectric effect, etc. Strikingly, ultrahigh LIVs of larger than 50 V was therefore achieved for the first time, orders higher than that of isostructural superconducting cuprate and three folds larger than that of reported largest values to date …”
Section: Introductionmentioning
confidence: 67%
“…Subject to long‐term endeavors, the involved origin of LIVs seems clearly stemming from the off‐diagonal term of the Seebeck tensor which is intrinsically associated with the anisotropy in structures, transport, and thermoelectric power, but in fact was determined or mainly achieved by the artificial film orientations . Abundant experimental methods and strategies or newly material system explorations, aiming at improving LIVs, therefore have been performed base on these points . For instance, A ‐site substitution with Ag in La 0.6 Pb 0.4 MnO 3 manganite, due to increasing the amount of Mn 4+ , could greatly enhanced electrical and magnetic transport properties which eventually favor anisotropic Seebeck enhancement .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation